2006
DOI: 10.1136/bmj.38856.692986.ae
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal mortality and congenital anomalies in babies of women with type 1 or type 2 diabetes in England, Wales, and Northern Ireland: population based study

Abstract: Objective To provide perinatal mortality and congenital anomaly rates for babies born to women with type 1 or type 2 diabetes in England, Wales, and Northern Ireland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
378
4
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 606 publications
(412 citation statements)
references
References 28 publications
19
378
4
11
Order By: Relevance
“…A systematic review examining the causes of stillbirth reported that chronic hypertension is associated with an increased risk with odds ratios of 1.5–2.7 [24]. Similarly, a UK national population-based cohort study of 2,359 pregnancies in women with diabetes mellitus reported a twofold increase in the risk of stillbirth compared to non-diabetic women [25]. A US population-based study reported that in pregnancies with preeclampsia the risk of stillbirth is increased by 70% [26].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review examining the causes of stillbirth reported that chronic hypertension is associated with an increased risk with odds ratios of 1.5–2.7 [24]. Similarly, a UK national population-based cohort study of 2,359 pregnancies in women with diabetes mellitus reported a twofold increase in the risk of stillbirth compared to non-diabetic women [25]. A US population-based study reported that in pregnancies with preeclampsia the risk of stillbirth is increased by 70% [26].…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmunologische Erkrankungen, wie das 7 Antiphospholipid-Syndrom, oder Erkrankungen, die mit einer Arteriosklerose einhergehen, sind hierfür Beispiele. Populationsbasierte Untersuchungen weisen bei Diabetes mellitus und arterieller Hypertonie auf eine Erhöhung des Risikos für eine Totgeburt um den Faktor 2-4 hin [10]. Die Assoziation von Thrombophilien mit Spätabort und intrauterinem Fruchttod zeigt .…”
Section: Cme (Weitgehend) Sichere Ursachen Für Totgeburtenunclassified
“…Sacral agenesis and caudal regression syndrome is almost pathognomonic of diabetes and occurs 256 times more often in diabetic than non-diabetic 13 .…”
Section: Introductionmentioning
confidence: 99%